Overview and new results from large-scale excavations in Schöningen. Issue 89 (December 2015) - Serangeli, Jordi; Böhner, Utz; Van Kolfschoten, Thijs; Conard, Nicholas J.
Abstract: Archaeological finds including spears, other wooden artifacts, lithic artifacts, and bones with impact scars and cut marks document the repeated presence of hominins on the shoreline of an approximately 300, 000 year old lake near Schöningen in Northern Germany. Continuing excavations have uncovered in the locality "Schöningen" at least 20 sites dating to the late Lower Paleolithic. Schöningen is therefore not only a singular archaeological site with remarkable finds; it is a vast locality that preserves a multifaceted archaeological landscape with numerous sites. Ongoing excavations have exposed several large surfaces with organic materials dating to MIS 9. In particular, recent excavations have uncovered new sections belonging to the original Spear Horizon from Schöningen 13 II-4 (the Horse Butchery Site). Current research in Schöningen places the exceptional artifacts within a spatial and environmental context, and provides a wealth of new information on the subsistence strategies and settlement dynamics of the inhabitants of these short-term lakeside occupations. Schöningen, with an overall excavated area of 9400 m 2, is one of the largest excavated archaeological localities from MIS 9. Here we present a summary of all the sites, as well as the most relevant excavated areas since 2008 (excavations Tübingen/NLD).